2019
DOI: 10.1007/s40487-019-00104-1
|View full text |Cite
|
Sign up to set email alerts
|

64Cu-DOTATOC PET-CT in Patients with Neuroendocrine Tumors

Abstract: Introduction: Several radiolabeled somatostatin analogues have been developed for molecular imaging of neuroendocrine tumors (NETs) with single-photon emission computed tomography (SPECT) and positron-emission tomography (PET). The aim of the present study was to report our first results using 64 Cu-DOTATOC in patients with NETs. Methods: Thirty-three patients with NETs (15 female, 18 male; mean age 64 ± 13 years) were included in this retrospective study. 64 Cu-DOTATOC PET-CT scans were performed on all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…More recent clinical studies, particularly head-to-head comparisons of [ 64 Cu]Cu-DOTA-TATE with both [ 111 In]In-DOTA-TATE [36] and [ 68 Ga]Ga-DOTA-TOC [37] revealed an overall better performance of the 64 Cu-conjugated in terms of sensitivity, resolution and rate of lesion detection. Additionally, other first-in-human studies with [ 64 Cu]Cu-DOTA-TOC also showed high lesion detection rate, safety of use and high effectiveness for predicting treatment planning [38]. Even more recently, Loft et.al.…”
Section: Introductionmentioning
confidence: 95%
“…More recent clinical studies, particularly head-to-head comparisons of [ 64 Cu]Cu-DOTA-TATE with both [ 111 In]In-DOTA-TATE [36] and [ 68 Ga]Ga-DOTA-TOC [37] revealed an overall better performance of the 64 Cu-conjugated in terms of sensitivity, resolution and rate of lesion detection. Additionally, other first-in-human studies with [ 64 Cu]Cu-DOTA-TOC also showed high lesion detection rate, safety of use and high effectiveness for predicting treatment planning [38]. Even more recently, Loft et.al.…”
Section: Introductionmentioning
confidence: 95%
“…Tables 1 and 2 show examples of medical uses and decay information for some of these pairs. For example, copper-64 ( 64 Cu) labeled DOTATATE ([ 64 Cu]Cu-DOTATATE) and [ 177 Lu]Lu-DOTATATE for NETs 37 . Different elements used to label a pharmaceutical are not guaranteed to have identical in vivo biological behavior in the body, but it is often assumed they do for treatment planning and dosimetry.…”
Section: Classes Of Theranostic Pairsmentioning
confidence: 99%
“…18 F is a radionuclide that has had increased focus for SSTR-targeting peptides [ 37 , 40 ]. It should be noted that other novel radiometals are currently in use and are continuously being investigated due to their similar advantages over 68 Ga, such as 64 Cu, 44 Sc and 89 Zr, with 64 Cu-DOTATOC and 64 Cu-DOTATATE currently being in clinical use as 68 Ga-DOTATOC and 68 Ga-DOTATATE alternatives [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. These radiometals also provide attractive alternatives to 68 Ga PET imaging, although they are beyond the scope of this review.…”
Section: Peptidesmentioning
confidence: 99%